Work-from-home (WFH) during COVID-19 Pandemic–A netnographic investigation using Twitter data - Daneshfar, Zahra; Asokan-Ajitha, Aswathy; Sharma, Piyush; Malik, Ashish (Emerald, 2022)
Purpose: This paper aims to create a better understanding of the challenges posed by work from home (WFH) during the ongoing COVID-19 pandemic, to investigate the public sentiment toward this transition, and to develop a conceptual model incorporating the relationships among the factors that influence the effectiveness of WFH.